Global Gridded Data on Climate Impact on Yields From DSSAT Crop Model, 2005–2050 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset presents percentage changes in agricultural yields due to climate change, comparing the projected yield in 2050 under two greenhouse gas emissions scenarios and 5 climate models, to the climate of 2005. The dataset includes spatially explicit outputs at a 0.5-degree resolution and covers seven key crops: maize, wheat, rice, soybeans, sorghum, groundnuts (peanuts), and potatoes. The analysis is done separately for growing under rainfed and irrigated conditions and includes separate results computed with and without CO2 fertilization. The yields used in the calculation were generated using the Decision Support System for Agrotechnology Transfer (DSSAT) crop model. The projections are driven by climate inputs from five global climate models (GCMs) included in the Inter-Sectoral Impact Model Intercomparison Project phase 3b (ISIMIP3b), aligned with the Coupled Model Intercomparison Project phase 6 (CMIP6). Two Shared Socioeconomic Pathways—SSP370 and SSP585—are used to represent divergent climate and development trajectories. Simulations were conducted both with and without the effects of carbon dioxide (CO₂) fertilization.